The Lick Observatory Supernova Search follow-up program: photometry data release of 70 SESNe. Issue 3 (17th March 2022) - Zheng, WeiKang; Stahl, Benjamin E; de Jaeger, Thomas; Filippenko, Alexei V; Wang, Shan-Qin; Gan, Wen-Pei; Brink, Thomas G; Altunin, Ivan; Baer-Way, Raphael; Bigley, Andrew; Blanchard, Kyle; Blanchard, Peter K; et al.
ABSTRACT: We present BVRI and unfiltered ( Clear ) light curves of 70 stripped-envelope supernovae (SESNe), observed between 2003 and 2020, from the Lick Observatory Supernova Search follow-up program. Our SESN sample consists of 19 spectroscopically normal SNe Ib, 2 peculiar SNe Ib, six SNe Ibn, 14 normal SNe Ic, 1 peculiar SN Ic, 10 SNe Ic-BL, 15 SNe IIb, 1 ambiguous SN IIb/Ib/c, and 2 superluminous SNe. Our follow-up photometry has (on a per-SN basis) a mean coverage of 81 photometric points (median of 58 points) and a mean cadence of 3.6 d (median of 1.2 d). From our full sample, a subset of 38 SNe have pre-maximum coverage in at least one passband, allowing for the peak brightness of each SN in this subset to be quantitatively determined. We describe our data collection and processing techniques, with emphasis toward our automated photometry pipeline, from which we derive publicly available data products to enable and encourage further study by the community. Using these data products, we derive host-galaxy extinction values through the empirical colour evolution relationship and, for the first time, produce accurate rise-time measurements for a large sample of SESNe in both optical and infrared passbands. By modelling multiband light curves, we find that SNe Ic tend to have lower ejecta masses and lower ejecta velocities than SNe Ib and IIb, but higher 56 Ni masses.